2013
DOI: 10.5560/znb.2013-3195
|View full text |Cite
|
Sign up to set email alerts
|

Ionogel Fiber Mats: Functional Materials via Electrospinning of PMMA and the Ionic Liquid Bis(1-butyl-3-methyl-imidazolium) Tetrachloridocuprate(II), [Bmim]2[CuCl4]

Abstract: Ionogel fiber mats were made by electrospinning poly(methylmethacrylate) (PMMA) and the ionic liquid (IL) bis(1-butyl-3-methyl-imidazolium) tetrachloridocuprate(II), [Bmim] 2 [CuCl 4 ], from acetone. The morphology of the electrospun ionogels strongly depends on the spinning parameters. Dense and uniform fiber mats were only obtained at concentrations of 60 to 70 g L −1 of polymer and IL mass combined. Lower concentrations led to a low number of poorly defined fibers. High voltages of 20 to 25 kV led to well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“… 40 A previous study by Bagdahn et al of a copper-based MIL-hybrid material showed a color change after the material was exposed to ammonia vapor. 41 For example, Fig. 8 shows the analysis of the absorbance of a layer of (C 4 Py) 2 [Ni 0.5 Zn 0.5 Cl 4 ] deposited on glass and exposed to nitrogen-assisted ammonia vapor.…”
Section: Resultsmentioning
confidence: 99%
“… 40 A previous study by Bagdahn et al of a copper-based MIL-hybrid material showed a color change after the material was exposed to ammonia vapor. 41 For example, Fig. 8 shows the analysis of the absorbance of a layer of (C 4 Py) 2 [Ni 0.5 Zn 0.5 Cl 4 ] deposited on glass and exposed to nitrogen-assisted ammonia vapor.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, electrospinability and fiber formation are strongly dependent on solution properties, as known from extensive studies of electrospinning from VOCs. For example, in electrospinning from VOCs, the proper chain entanglement, required for fiber stretching, is regulated by viscosity, polymer concentration, and polymer molecular weight (MW), while the surface tension and conductivity of the solution direct the formation of either fibers or droplets. The electrical conductivity of the solution can be tuned by addition of conductive additives to electrospinning solutions such as inorganic salts (e.g., KH 2 PO 4 , NaCl) or organic salts (ILs, e.g., hexamethylimidazolium chloride, 1-ethyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium phosphate) which improves both spinability and fiber formation of a polymer from VOCs. It has also been shown that incorporation of ILs into a VOC–polymer solution prior to an electrospinning process results in hybrid “ionogel” materials, where the ILs stays entrapped within the electrospun biopolymeric matrix. …”
Section: Introductionmentioning
confidence: 99%